Perfiles de estudiantes y violencia filioparental: una identificación a través del análisis jerárquico lineal - Santos Villalba, María Jesús; Matas Terrón, Antonio; Alcalá del Olmo Fernández, María José; Leiva Olivencia, Juan José (Prisma social, 2021)
Child-to-Parent Violence (CPV) is an emerging line of research in the disciplines of psychology and pedagogy, given its current impact. This type of violence has experienced a remarkable increase in the number of cases in recent years in all segments of youth, which has been aggravated by the pandemic situation. The aim of this study was to identify the profiles that can be found in Spanish Andalusian youths in relation to CPV, taking into account cognitive, social and affective aspects, as well as the son's and daughter's own violent behaviour. In order to respond to this main objective, an analysis of the psychometric properties of the ad hoc questionnaire used to collect information was carried out. A sample of 478 adolescents from three schools in Andalusia (Spain) was studied. The cluster analysis shows a group with difficulties in handling and resolving family conflicts, and a second group with greater conflict management capacity. This study concludes on the importance of parenting style and family dynamics as key elements in preventing the triggering of CPV-associated behaviours.
Student profiles and child to parent violence: identification through hierarchical linear modeling
Keywords: child-to-parent violence; teenagers; psychosocial profiles; family relationships; Emerging; Scopus